Avaliação do consumo de água no sistema de irrigação por inundação com distribuição de múltiplas entradas na cultura de arroz (Oryza sativa L.) - Pineda Suárez, Darío Fernando [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Rice is the most consumed cereal worldwide and flood irrigation method is the most used due to the agronomic conditions that not only favor higher productivity, but also higher water consumption. Therefore, the objective objective of this study was to evaluate water consumption in an irrigation system with multiple inlet distribution in the rice culture. The work was developed during crop 2013/14 in the lowland area of the Rural Engineering Department at the School of Agronomical Sciences of São Paulo State University “Júlio de Mesquita Filho” University, Botucatu Campus- São Paulo. The method of irrigation for rice culture used in the experiment was the intermittent flood with water depth flood of 10 cm. The analysis of water consumption was made by comparing the input and output components of the water balance in the irrigated rice in two treatments, called MIRI for the irrigation treatment by distribution of multiple inlet, and CONV for the conventional flooded treatment. Input components for each treatment were rainfall and irrigation; and output components were the crop evapotranspiration (ETc), deep percolation and lateral flow. Rainfall measurement was made by a Rain Gauge through daily readings. Measuring the amount irrigation water applied was made by flowmeters of nominal flow rate of 15 m3 h–1. The daily calculation of ETc was made by the class A evaporimeter tank method; water losses by deep percolation, and lateral flow was made by measuring the elevation of the water table and the relation between the irrigated perimeter area and height of the levee, respectively. To determine the water content in the soil the Time Domain Reflectometry method was used, measuring on field with TDR100 equipment. The total water consumption in the treatment MIRI was of 1.754,8 mm, which is 8,62 % lower than CONV treatment, 4 mainly due to decreased irrigation water applied, which was 9,75% lower ...

O Arroz é o cereal mais consumido no mundo e o método de irrigação por inundação é o mais empregado devido às condições agronômicas criadas que favorecem à obtenção de maior produtividade mas também a maior consumo de água. Portanto o objetivo deste estudo foi avaliar o consumo de água no sistema de irrigação com distribuição de múltipla entrada na cultura do arroz, a qual foi desenvolvido durante a safra agrícola 2013/14 na área da várzea do Departamento de Engenharia Rural da Faculdade de Ciências Agronômicas da Universidade Estadual Paulista “Júlio de Mesquita Filho”, no campus Botucatu-SP. A irrigação do arroz no experimento foi realizada pelo método de irrigação por inundação intermitente dos tabuleiros e com altura de lâmina de água de 10 cm. A análise do consumo de água foi mediante a comparação dos componentes de entrada e saída do balanço hídrico em arroz irrigado com dois tratamentos, denominados MIRI para o tratamento de irrigação por distribuição de múltipla entrada e CONV para o tratamento de inundação convencional. Os componentes de entrada para cada tratamento foram a precipitação pluvial e lâmina de água de irrigação e os componentes de saída, a evapotranspiração da cultura (ETc), a percolação profunda e o fluxo lateral. Para a medição da precipitação pluvial foi usado um pluviômetro mediante leituras diárias e para a medição da lâmina de água aplicada na irrigação foram utilizados hidrômetros de vazão nominal de 15 m3 h-1. O cálculo diário da ETc foi pelo método de tanque evaporímetro classe A, as perdas de água por percolação profunda e fluxo ...
Keywords: Arroz - Irrigação; Balanço hidrológico; Agua - Uso; Eficiência do uso da água; Water efficiency